If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + -5) = 18 Reorder the terms: 3(-5 + y) = 18 (-5 * 3 + y * 3) = 18 (-15 + 3y) = 18 Solving -15 + 3y = 18 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 3y = 18 + 15 Combine like terms: -15 + 15 = 0 0 + 3y = 18 + 15 3y = 18 + 15 Combine like terms: 18 + 15 = 33 3y = 33 Divide each side by '3'. y = 11 Simplifying y = 11
| -2/9(3/1-4/9) | | 9x+-2=1 | | -7a=6 | | 32x-6=25x | | 93-6x=30x+17 | | -18=12a | | (5)/(6)-(1)/(3)=3 | | y-(-9)=-2/9(3-4/9) | | 5=13t | | 9x/x^2+8x | | r^3-8r^2+16r^2=0 | | 7x^2-265x-600=0 | | 4m+2=29-2m | | -3(x-7)(x-8)= | | 7x^2-265t-600=0 | | -8b=-13 | | -6y-9=2y+15 | | 4y-12=y-12 | | x+2y-3z=9 | | X+24+2x=-19-2x-22 | | -9w=-12 | | -2a+8+6a=9a-3a | | 5a=-2 | | 18x^3-27x= | | 52+5y-21=17y-14-3y | | 3x+4/2x+3=x+14/x+8 | | 20=-6a | | x+3/x+1=x-3/x-8 | | -7r=6 | | 4z-15-z+3=0 | | 62-5x=10x+18 | | -6x=9 |